Logic of Long: how to understand the continuities and changes in Chinese foreign policies - Kaisheng, Li (2019)
Chinese foreign policies are usually investigated based on the conception that China is a socialist and rising power. The tradition factors are thus overlooked or even distorted. In fact, the foreign policies of socialist China has been shaped and influenced by the traditional factors such as history and culture. National revival as the total international goal is rooted deeply in Chinese double memories of great civilization and humiliation century. Its policy approaches have been influenced the strategic culture of Wangdao. The combination of traditional factors and contemporary conditions such as personal, national and international factors has shaped together the foreign policies of socialist China since 1949. Based on this logic, there have been the astonishing continuities in China’s foreign policies from Chairman Mao to President Xi while some changes happened in the level of policy approach.